Alkoxylalkyl Esters of Nucleotide Analogs Inhibit Polyomavirus DNA Replication and Large T Antigen Activities - Onwubiko, Nichodemus O; Diaz, Suraya A; Krečmerová, Marcela; Nasheuer, Heinz Peter (Antimicrobial agents and chemotherapy, 2021)
Polyomavirus infections occur commonly in humans and are normally nonfatal. However, in immunocompromised individuals, they are intractable and frequently fatal. Due to a lack of approved drugs to treat polyomavirus infections, cidofovir, a phosphonate nucleotide analog approved to treat cytomegalovirus infections, has been repurposed as an antipolyomavirus agent. Cidofovir has been modified in various ways to improve its efficacies as a broad-spectrum antiviral agent. However, the actual mechanisms and targets of cidofovir and its modified derivatives as antipolyomavirus agents are still under research. Here, polyomavirus large tumor antigen (Tag) activities were identified as the viral target of cidofovir derivatives. The alkoxyalkyl ester derivatives of cidofovir efficiently inhibit polyomavirus DNA replication in cell-free human extracts and a viral in vitro replication system utilizing only purified proteins. We present evidence that DNA helicase and DNA binding activities of polyomavirus Tags are diminished in the presence of low concentrations of alkoxyalkyl ester derivatives of cidofovir, suggesting that the inhibition of viral DNA replication is at least in part mediated by inhibiting single-stranded DNA (ssDNA) and double-stranded DNA (dsDNA) binding activities of Tags. These findings show that the alkoxyalkyl ester derivatives of cidofovir are effective in vitro without undergoing further conversions, and we conclude that the inhibitory mechanisms of nucleotide analog-based drugs are more complex than previously believed.
Keywords: cytosin; DNA helicase; nukleotidy; polyomavirus; nucleoside analogs; Esters; DNA, Viral; Cytosine; lidé; replikace viru; replikace DNA; Antigens, Viral, Tumor; Polyomavirus; protein-DNA interactions; Nucleotides; antigeny virové nádorové; DNA replication; large T antigen; estery; ATPase; Virus Replication; DNA Replication; DNA virů; Humans